1994
DOI: 10.1007/s001250050068
|View full text |Cite
|
Sign up to set email alerts
|

Aminoguanidine inhibits the development of accelerated diabetic retinopathy in the spontaneous hypertensive rat

Abstract: Summary Arterial hypertension has been identified as a major secondary risk factor for diabetic retinopathy. However, the mechanisms by which hypertension worsens retinopathy are unknown. Inhibition of advanced glycation product formation prevents the development of experimental diabetic retinopathy in normotensive diabetic rats. In this study the effect of hypertension on the rate of diabetic retinopathy development and the formation of arteriolar thrombosis was evaluated. We also evaluated the effect of amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 14 publications
0
46
0
1
Order By: Relevance
“…[36][37][38][39] AG reacts with biological compounds with carbonyl groups, 40) and therefore it was suggested that AGE formation is inhibited by reaction with Amadori-derived compounds, including 3-deoxyglucosone. 40) In the present study, it was found that methylglyoxal reacted earlier with AG than guanidino compounds.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39] AG reacts with biological compounds with carbonyl groups, 40) and therefore it was suggested that AGE formation is inhibited by reaction with Amadori-derived compounds, including 3-deoxyglucosone. 40) In the present study, it was found that methylglyoxal reacted earlier with AG than guanidino compounds.…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable debate about the physiopathological signi®cance of these observations. Because formaldehyde is an angiotoxic compound, the high levels of both MET and Bz-SSAO may have a role in the cardiovascular degeneration observed in diabetes, and may contribute to explaining the favourable e ects of Bz-SSAO inhibitors in this pathology (Lyles & McDougall, 1989;Hammes et al, 1994;Yu & Zuo, 1997;Ekblom, 1998). Moreover, in considering the hypophagic e ect of MET, it can also be hypothesized that the increased levels of this aliphatic amine in diabetes represent a part of the physiological mechanisms involved in the control of hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Hammes et al have reported in both normotensive [8] and hypertensive [36] diabetic rats that aminoguanidine prevented the development of retinopathy, characterised by acellular capillaries and pericyte loss. The co-localisation of AGEs and RAGE within the retina may represent a ligand-receptor interaction involved in the genesis of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%